Genotype-Specific ECG-Based Risk Stratification Approaches in Patients With Long-QT Syndrome - Rieder, Marina; Kreifels, Paul; Stuplich, Judith; Ziupa, David; Servatius, Helge; Nicolai, Luisa; Castiglione, Alessandro; Zweier, Christiane; Asatryan, Babken; Odening, Katja E. (Frontiers in Cardiovascular Medicine, 2022)
Background: Congenital long-QT syndrome (LQTS) is a major cause of sudden cardiac death (SCD) in young individuals, calling for sophisticated risk assessment. Risk stratification, however, is challenging as the individual arrhythmic risk varies pronouncedly, even in individuals carrying the same variant. Methods: In this study, we aimed to assess the association of different electrical parameters with the genotype and the symptoms in patients with LQTS. In addition to the heart-rate corrected QT-interval (QTc), markers for regional electrical heterogeneity such as QT dispersion (QTmax-QTmin in all ECG leads) and delta Tpeak/end (Tpeak/end V5 – Tpeak/end V2) were assessed in the 12-lead ECG at rest and during exercise testing. Results: QTc at rest was significantly longer in symptomatic than asymptomatic LQT2 patients (493.4ms ± 46.5ms vs. 419.5ms ± 28.6ms, p=0.004), but surprisingly not associated with symptoms in LQT1. In contrast, post-exercise QTc (4 min of recovery) was significantly longer in symptomatic than asymptomatic LQT1 patients (486.5ms ± 7.0ms vs. 463.3ms ± 16.3ms, p=0.04), while no such difference was observed in LQT2 patients. Enhanced delta Tpeak/end and QT dispersion were only associated with symptoms in LQT1 (delta Tpeak/end 19.0ms ± 18.1ms vs. -4.0ms ± 4.4ms, p=0.02; QT-dispersion: 54.3ms ± 10.2ms vs. 31.4ms ± 10.4ms, p=0.01), but not in LQT2. Delta Tpeak/end was particularly discriminative after exercise, where all symptomatic LQT1 patients had positive and all asymptomatic LQT1 negative values (11.8ms ± 7.9ms vs. -7.5ms ± 1.7ms, p=0.003). Conclusion: Different electrical parameters can distinguish between symptomatic and asymptomatic patients in different genetic forms of LQTS. While the classical “QTc at rest” was only associated with symptoms in LQT2, post-exercise QTc helped distinguish between symptomatic and asymptomatic LQT1 patients. Enhanced regional electrical heterogeneity was only associated with symptoms in LQT1, but not in LQT2. Our findings indicate that genotype-specific risk stratification approaches based on electrical parameters could help to optimize risk assessment in LQTS.